THU0007 Microrna-155/PU.1 Axis as an Epigenetic Regulator of B-Cell Activation in Rheumatoid Arthritis. (9th June 2015) - Alivernini, S.; Tolusso, B.; Kurowska-Stolarska, M.; Canestri, S.; Benvenuto, R.; Mangoni, A.; Fedele, A.L.; Petricca, L.; Gremese, E.; McInnes, I.B.; Ferraccioli, G.
Abstract : Background: MicroRNA-155 (miR-155) has been shown to be a key regulator of B cell biology. The regulation of the transcription factor PU.1 by miR-155 is required for high-affinity IgG1 production and B cell maturation. However, the role of miR-155 in the activation of B in Rheumatoid Arthritis (RA) has not been explored. Objectives: To investigate miR-155 expression in RA B cells and its association with B cell activation and synovial inflammation. Methods: 53 RA patients underwent synovial (ST) biopsy. ST samples were categorized on a basis of immunostaining for CD68, CD21, CD3 and CD20 cells as diffuse or aggregate pattern. MiR-155 expression in RA ST was evaluated by in situ hybridization (ISH)(n=15). B cells from peripheral blood (PB) and matched synovial fluid (SF) of RA (n=19) and PB of healthy controls (HC)(n=10) were isolated by CD19+ microbeads. B-cell subsets were determined through Flow-Cytometry. IL-6 and BAFF levels in PB and SF were measured by ELISA. MiR-155 and PU.1 expression was determined by qPCR in B cells from PB and SF of RA (n=10) and on ST samples of osteoarthritis (OA)(n=3), RA diffuse (n=8) and RA aggregate (n=8) patients. Finally, HC PB B cells (n=5) were cultured with or without IL-6 (30ng/ml) or BAFF (20ng/ml) and miR-155 and PU.1 expression was assessed by qPCR. Results: 23 (43, 4%) RA patients had an aggregate pattern of ST biopsy. RA with an aggregate pattern were more likely anti-CCP+ compared to RA with diffuse pattern (p=0.04).Moreover, anti-CCP plasma levels directly correlated with the synovial aggregate grade (r=0.39; p=0.01). IL-6 and BAFF levels were higher in SF than in PB of RA regardless of the synovial infiltrate pattern (p=0.001 for both). ISH showed that miR-155 was expressed at significantly higher levels in ST of aggregate RA compared to diffuse RA (p=0.03). qPCR further confirmed that miR-155 was significantly increased in ST of aggregate RA compared to diffuse RA (p=0.03) and OA (p=0.03) respectively. Consistently, PU.1 staining was found to be lower within synovial lymphoid aggregates in RA patients. On the single cell level, miR-155 was expressed significantly higher in RA PB B-cells compared to HC (p=0.0002). In addition, miR-155 was over-expressed in SF B-cells compared to matched PB B-cells (p=0.05) in RA. Consistently, PU.1 expression was lower in SF B-cells compared to matched PB B-cells (p=0.001). Moreover, anti-CCP+ RA showed higher miR-155 expression in PB B-cells compared to anti-CCP- RA (p=0.02) and HC (p=0.001). CD19+/IgD-CD27- cells were significantly over-represented in PB of aggregate compared to diffuse RA (p=0.04). Finally, IL-6 and BAFF in vitro stimulation of HC B-cells induced miR-155 overexpression (p=0.04 and p=0.03) whereas PU.1 was significantly down-regulated (p=0.01 and p=0.03). Conclusions: MiR-155 is over-expressed in B-cells of RA and is associated to anti-CCP positivity, an aggregate synovial pattern and a PU.1 lower expression. IL-6 and BAFF are significantly increased in the SF environment and induce in vitro miR-155 expression in B-cells. Thus, miR-155 may represent a key regulator of B-cells in RA patients with a memory phenotype. Disclosure of Interest: None declared